Le Libertaire : organe anarchiste (Liège: Groupe Socialisme libertaire)
"Periodiciteit: maandelijksRedactie: rue Vivegnis 220, Liège / Jean Vallon / F. Zachary (éditeur responsable), rue Ferrer 9, Seraing"